Budidaya Sagu sebagai Pilar Utama Penghidupan Masyarakat Lokal di Kampung Baingkete - Ponisri, Ponisri; Farida, Anif; Hasa, Muh. Fadli; Darma, Darma; Mangallo, Bertha; Murtiningrum, Murtiningrum; Abu, Nur (Penerbit Goodwood, 2023)
Purpose: The activities about sustainable sago cultivation techniques aim to increase knowledge and understanding of the Women's Fellowship and PKK farmer groups in the field of sago cultivation. This is because sago is the staple food of the local community in Baingkete and its surroundings. By increasing sago production, it is hoped that it can improve community welfare and reduce dependence on imported food ingredients. Research methodology: The methods applied in this activity include counseling (providing knowledge and understanding about sago cultivation), demonstration and training (direct practice of planting sago on land owned by farmer groups), discussion and consultation, and program evaluation (giving statements to participants before and after training). Result: The results of the activity showed that the participants were quite enthusiastic about asking questions regarding sago cultivation. They are also very active during the practice of planting sago on the land. The level of community knowledge about sago planting techniques has increased about 25%. Training, practice, and field assistance related to sago cultivation also increased from 40% to 85%. Limitation : The practice of sago cultivation techniques is carried out on 1 ha of agricultural land. And knowing how to increase sago production cannot be done immediately considering the length of time the sago plant grows until it can be harvested. Contribution: This activity is beneficial for the community, which learns about sustainable and environmentally friendly sago cultivation practices. This includes sustainable soil management techniques, the use of organic fertilizer, and the maintenance of a healthy ecosystem.